Effect of an intensive non-invasive program including spinal decompression on MRI-assessed structural changes in cervical disc herniation - Vincenzo Di Modica; Giuseppe J. Sciarrone (Interdisciplinary Neurosurgery)
Background: Despite the critical role of the cervical spine, evidence describing the effectiveness of specific non-invasive protocols for treating cervical disc herniation (CDH) remains limited, even though these approaches are often preferred over surgical solutions. The aim of the present case series study is to present the results of an intensive non-invasive treatment program primarily based on non-surgical spinal decompression (NSSD) therapy, evaluated using objective MRI image processing methods. Materials and methods: Three subjects diagnosed with CDH through MRI, exhibiting radiculopathy symptoms, and unresponsive to standard physiotherapy, participated in an extensive non-invasive treatment protocol lasting for a period ranging from three to five months. Progress was monitored by quantitative evaluation of structural changes observed on MRI scans taken before and after treatment. Results: Quantitative indicators confirmed an improvement in the extent of CDH in all patients who underwent the intensive treatment program, ranging from approximately 32% to 55%. Conclusions: This case series suggests that an intensive, non-invasive protocol incorporating NSSD therapy may promote symptom relief in CDH, with MRI observations indicating possible structural changes. However, due to inherent study limitations, generalizable conclusions or assessments of NSSD’s overall efficacy for CDH cannot be established. Larger-scale investigations, with expanded patient cohorts and a control group, are needed to validate these preliminary findings and determine the therapeutic impact of NSSD on CDH with greater accuracy.